Weekly long-acting growth hormone versus daily growth hormone therapy on quality of life, efficacy, and safety in children with short stature: a systematic review and meta-analysis - Fan Liu; Linying Xiu; Wei Zhang; Chunhui Zang; Shuyu Wang (Frontiers in Endocrinology, 2026)
Background This meta-analysis aims to compare the QoL, efficacy, and safety of once-weekly LAGH versus daily GH in children with short stature. Methods We systematically searched PubMed, Embase, the Cochrane Library, and Web of Science from inception to June 30, 2026, for studies comparing LAGH with daily GH in children with short stature. Outcomes of interest encompassed QoL, efficacy, and safety. Pooled analyses were conducted using a random-effects model. Treatment effects for continuous and dichotomous variables were expressed as weighted mean differences (WMDs) and risk ratios (RRs), respectively, each with 95% confidence intervals (CIs). Results Thirty studies (27 cohorts) comprising 3,287 patients were included. Available QoL data from two major trials indicated comparable improvements between treatment groups, with a trend toward greater clinical benefit in psychosocial domains observed for a higher dose of Somapacitan. Regarding efficacy, no statistically significant differences were found between groups for height velocity (WMD: 0.26; 95% CI: -0.07 to 0.58; P = 0.124), height standard deviation score (SDS) (WMD: 0.04; 95% CI: -0.03 to 0.10; P = 0.285), or the ratio of bone age to chronological age (BA/CA) (WMD: 0.00; 95% CI: -0.01 to 0.01; P = 0.999). However, the LAGH group exhibited a significantly greater increase in insulin-like growth factor 1 (IGF-1) SDS compared to the daily GH group (WMD: 0.37; 95% CI: 0.13 to 0.62; P = 0.003). Subgroup analyses suggested that efficacy may be influenced by the specific LAGH formulation and baseline patient characteristics. The safety analysis revealed a comparable overall risk of adverse events between groups (RR: 1.02; 95% CI: 0.97 to 1.08; P = 0.468). Conclusion Once-weekly LAGH demonstrates comparable efficacy and a similar overall safety profile to daily GH in children with short stature. By reducing injection frequency, LAGH offers the potential to enhance treatment convenience and adherence, which may translate into improved QoL. Further long-term studies are warranted to confirm these findings and to investigate formulation-specific effects.